2014
DOI: 10.1128/aem.01883-14
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Novel Polycyclic Aromatic Hydrocarbon Dioxygenases from the Bacterial Metagenomic DNA of a Contaminated Soil

Abstract: f Ring-hydroxylating dioxygenases (RHDs) play a crucial role in the biodegradation of a range of aromatic hydrocarbons found on polluted sites, including polycyclic aromatic hydrocarbons (PAHs). Current knowledge on RHDs comes essentially from studies on culturable bacterial strains, while compelling evidence indicates that pollutant removal is mostly achieved by uncultured species. In this study, a combination of DNA-SIP labeling and metagenomic sequence analysis was implemented to investigate the metabolic p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(19 citation statements)
references
References 40 publications
0
18
0
Order By: Relevance
“…Environmental biologists deem microbial bioremediation to be one of the potent tools to eliminate environmental contaminants (Bell et al, 2014 ; Chemerys et al, 2014 ; Roling, 2015 ). A number of review articles have recently been published and provide a much detailed account about the role of multi-omics (metagenomics, proteomics, metatranscriptomics, metabolomics, and fluxomics) approaches in microbial bioremediation.…”
Section: Success Stories: Omics-approaches In Microbial Bioremediatiomentioning
confidence: 99%
“…Environmental biologists deem microbial bioremediation to be one of the potent tools to eliminate environmental contaminants (Bell et al, 2014 ; Chemerys et al, 2014 ; Roling, 2015 ). A number of review articles have recently been published and provide a much detailed account about the role of multi-omics (metagenomics, proteomics, metatranscriptomics, metabolomics, and fluxomics) approaches in microbial bioremediation.…”
Section: Success Stories: Omics-approaches In Microbial Bioremediatiomentioning
confidence: 99%
“…Environmental scientists consider metagenomic bioremediation as one of the potential tools to remove contaminants from the environment [13][14][15]. As cited earlier, recent multiple studies have reported metagenomic approaches in bioremediation.…”
Section: Applications Of Metagenomics In Bioremediationmentioning
confidence: 99%
“…Metagenomic analysis showed a great abundance of aromaticring-hydroxylating oxygenase (RHO) genes, which were potentially responsible for polycyclic aromatic hydrocarbon (PAH) biodegradation, in uncultured microorganisms in chronically-polluted coastal sediments (Loviso et al 2015). Exploitation of metagenomic data has proved to be beneficial for the enzymatic characterization of RHOs from yet-to-becultured microorganisms in polluted soils (Singleton et al 2012;Martin et al 2013;Chemerys et al 2014) and marine environments (Musumeci et al 2019) providing a better understanding of the catabolic versatility of the vast majority of uncultured microbes. Dong and collegues used shotgun metagenomics to discover uncultured bacterial and archaeal phyla capable of the anaerobic degradation of aliphatic and aromatic hydrocarbons from deep-sea sediments.…”
Section: Exploring the Environmental Potential Of Uncultivated Bacteriamentioning
confidence: 99%